Agent-based modelling and swarming in urban architecture : simulating urban environment - Gomes, Tiago André Martins (2016)
The focus of this research is to present a method to understand complexity within our cities from the standpoint of the Social Sciences and Urban Architecture itself while making use of Agent-Based Modelling and Swarm Intelligence computational methods based on simple theoretical models of self-organization to allow the exploration of, otherwise, imperceptible qualities within urban space as a complex network. These methods provide an overview on how the human element in the urban environment behaves in a dynamic way and how the city operates from its core individual entities as an emergent complex system built upon architectural elements and society rules as well as basic human rules of motion. Due to its non-linear approach to these non-linear concepts and principles, the structure of this dissertation takes several moments of exploration throughout its course along with the development of a computer program that keeps up with these constantly evolving principles and immaterial qualities. What is then materialized through the adaptive application are complex abstract shapes that are perceived and translated into context specific non-tangible spatial features. Is a space open or closed? How close or how open? Maybe both? Or time-based features like flow/flux and tendency paths, like positive, negative, constrained, loose, etc. These are some of the expected translations that will take place in the closing statement of this dissertation How these sets of features can be perceived translated and thought upon on a context- specific urban space are the main motivation of this work in a physical and in an abstract manner. Both objectives of this research were fulfilled by providing a constantly developing tool that uses the potential of agent based and swarming models for simulation and urban space analysis and perceive emergent proprieties within urban and social space that are complex by nature as well as to review its potential in the integration with architecture’s cultural techniques and practices.